The whole-brain child : 12 revolutionary strategies to nurture your child's developing mind - Siegel, Daniel J., 1957-; Bryson, Tina Payne (Delacorte Press, 2011)
Your toddler throws a tantrum in the middle of a store. Your preschooler refuses to get dressed. Your fifth-grader sulks on the bench instead of playing on the field. Do children conspire to make their parents' lives endlessly challenging? No -- it's just their developing brain calling the shots! In this book, Daniel J. Siegel, neuropsychiatrist, and parenting expert Tina Payne Bryson demystify the meltdowns and aggravation, explaining the science of how a child's brain is wired and how it matures. The "upstairs brain," which makes decisions and balances emotions, is under construction until the mid-twenties. And especially in young children, the right brain and its emotions tend to rule over the logic of the left brain. No wonder kids can seem -- and feel -- so out of control. By applying these discoveries to everyday parenting, you can turn any outburst, argument, or fear into a chance to integrate your child's brain and foster vital growth.